Reading the social body - Burroughs, Catherine B., 1958-; Ehrenreich, Jeffrey (University of Iowa Press, 1993)
The overarching argument of Reading the Social Body is that the body is cultural rather than "natural." Some of the essays treat the social construction of bodies that have actually existed in human history; others discuss the representation of bodies in artistic contexts; all recognize that everything visible to the human body--from posture and costume to the width of an eyebrow or a smile--is determined by and shaped in response to a particular culture